2013
DOI: 10.1111/ctr.12270
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of nosocomial pneumonia and risk of recurrence after antimicrobial therapy in critically ill lung and heart–lung transplant patients

Abstract: Little is known about the resolution of symptoms of nosocomial pneumonia (NosoP) after lung and heart-lung transplantation. The aim of this study was to describe the clinical response to antimicrobial therapy in (ICU) patients with NosoP after lung or heart-lung transplantation. Between January 2008 and August 2010, 79 lung or heart-lung transplantations patients were prospectively studied. NosoPwas confirmed by quantitative cultures of bronchoalveolar lavage or endotracheal aspirates. Clinical variables, sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 36 publications
2
19
1
Order By: Relevance
“…Also in accordance with previous studies [10,38,39], pre-transplant colonisation was not associated with a higher incidence of ventilator-associated respiratory infection and patients with cystic fibrosis (despite the fact that they were all colonised, frequently by multidrug-resistant organisms) did not present more episodes of VAT or VAP than the rest of the population. The same was true for all the other underlying diseases.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Also in accordance with previous studies [10,38,39], pre-transplant colonisation was not associated with a higher incidence of ventilator-associated respiratory infection and patients with cystic fibrosis (despite the fact that they were all colonised, frequently by multidrug-resistant organisms) did not present more episodes of VAT or VAP than the rest of the population. The same was true for all the other underlying diseases.…”
Section: Discussionsupporting
confidence: 91%
“…Multidrug-resistant bacteria are common in lung transplant recipients [10,25]. In our patients, multidrug-resistant P. aeruginosa was the most frequent microorganism in the patients with VAP, and was also common in those with VAT.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Nosocomial pneumonia is observed in 47% lung transplant recipients during their ICU stay, and 40% of patients who had nosocomial pneumonia had pneumonia recurrence. 29 Most frequently isolated organisms were Enterobacteriaceae, Pseudomonas aeruginosa, and Staphylococcus aureus. Another retrospective study reported that in lung transplant recipients, new pulmonary infiltrates occurring after the first month are most likely due to infection, with bacterial pathogens responsible in 50% pneumonias.…”
Section: Infectious Respiratory Complicationsmentioning
confidence: 99%